시간 동기 방식의 OTP를 이용한 디지털 도어락 시스템 - 황형진(Hyung-Jin Hwang); 김권양(Kweon-Yang Kim); 하일규(Il-Kyu Ha) (한국정보통신학회논문지, 2017)
Recently, OTP (One-time-Password) log-in methods have been used in many areas to prevent leakage of personal information and enhance security. The OTP method is primarily used for security of bank personal account, this is one of the sophisticated security ways in which one time password is generated and checked to enhance security. Digital door locks frequently used in everyday life require convenience and safety simultaneously. Meanwhile, related technologies for digital door locks are evolving, but methods for enhancement of security are still unsatisfactory. Generally, the digital door lock using password input type has been most commonly used and especially it provides more convenience, but it has some problems such as password exposure and password oblivion. Therefore, in this study, we propose and implement the OTP-based digital door lock system with enhanced security and convenience features but without the risk of password exposure and oblivion. 최근 들어 개인 정보 유출을 방지하고, 보안을 강화하기 위하여 OTP (One-time- Password)를 이용한 로그인 방법을 많이 사용하고 있다. OTP 방식은 은행의 개인 계정 보안을 위하여 주로 사용되어온 방법으로 일회용 비밀번호를 받아 사용하는 보안성이 강화된 방법 중 하나이다. 한편, 일상생활에서 자주 사용하는 디지털 도어락은 편의성과 보안성을 동시에 요구한다. 디지털 도어락에 관한 관련 기술이 발전하고 있지만 아직 보안성에는 취약한 것이 사실이다. 특히, 가장 흔하게 사용되고 있는 비밀번호 입력 방식의 디지털 도어락은 편의성을 제공하지만 비밀 번호 노출, 망각 등과 같은 부작용이 따르게 된다. 따라서 본 연구에서는 비밀 번호 노출과 망각의 위험이 없는 보안성과 편의성이 강화된 OTP 기반의 디지털 도어락 시스템을 제안하고 구현한다.